Paolo Sylos Labini: Reflections of a Classical Economist - Zacchia, Giulia (PSL Quarterly Review, 2016)
The article provides a review of Sylos Labini’s memories, collected here on occasion of the tenth anniversary of his passing away. The author reports on the proceedings of two conferences in memory of Sylos Labini held in Rome, on 18 November 2015 at the Lincean Academy and on 4 December 2015 at Sapienza University. Sylos Labini stipulated that the goal of economic development is not just to satisfy human needs, but to cater civil development itself, in accordance with Adam Smith’s fundamental lesson. In his view, economic development and civil development interact in a circular manner in the long run. Considering the developmental issues of Italy’s Mezzogiorno, Sylos Labini highlights that the nature of the problem is not only economic, but rather many issues arise from unreasonable links between politics, economy, and society. Accordingly, he provided policy suggestions that are not limited to the economic and industrial fields (such as water supply projects, irrigation infrastructures, and investments for the creation of modern industries), but he also identified three priority areas of social policy: measures to contrast the mafias, crime in public procurement, and corruption; a reform of the public administration; and investments in education, universities, and research. JEL: B31, A11, N14, A12